2021
DOI: 10.3389/fpsyg.2020.624189
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Organizational Social Capital and Product Innovation: The Mediating Role of Realized Absorptive Capacity

Abstract: This paper examines the influence on product innovation of factors based on a company’s transformation and exploitation of knowledge gathered from its intra-organizational relationships. Specifically, this paper analyses the influence of intra-organizational social capital (SC) (i.e., comprised of structural, relational, and cognitive dimensions) on realized absorptive capacity (RACAP). Moreover, it analyses the mediating role of RACAP on the relationship between internal SC and product innovation. Based on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 96 publications
3
8
0
2
Order By: Relevance
“…From an intraorganizational network perspective, higher ACAP of business units is associated with higher innovation performance (Ortiz et al, 2020). This observation is in line with the proposition of Zahra and George (2002) that PACAP and RACAP act as a source of a firm's innovativeness.…”
Section: The Direct and Moderated Impacts Of An Sme's Acap In The Operation Stage On Cn Innovation Performancesupporting
confidence: 81%
“…From an intraorganizational network perspective, higher ACAP of business units is associated with higher innovation performance (Ortiz et al, 2020). This observation is in line with the proposition of Zahra and George (2002) that PACAP and RACAP act as a source of a firm's innovativeness.…”
Section: The Direct and Moderated Impacts Of An Sme's Acap In The Operation Stage On Cn Innovation Performancesupporting
confidence: 81%
“…According to Pinkse et al (2010), shared AC of workers can facilitate their common understanding of the collaborative tasks in the specific context. Moreover, a common understanding of the collaborative tasks will foster trust and strong links between different workers (Ortiz et al, 2021). Similar to the processes, whereby AC occurs at the organizational level mentioned in H1, individual AC processes also correspond to those of participating, establishing identity and practicing in a community of practice.…”
Section: Collaboration In Bim-enabled Projectsmentioning
confidence: 91%
“…Previous literature has revealed the multilevel nature of NPD team's creativity nested from organizational/structural level to individual/psychological level. For example, Ortiz et al ( 2021 ) demonstrated that organizational factors such as internal social capital and absorptive capacity improved the creativity of NPD teams, which in turn had a positive effect on the bottom line of firms. Such nested creativity within an organization was also addressed with the notion of person-environment fit (Wang and Wang, 2018 ), suggesting that the congruency between supportive environment for creativity of an organization and creativity of employees improved the process and outcome of NPD.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%